Bioinformatics analysis of tumor-educated platelet microRNAs in patients with hepatocellular carcinoma. Issue 12 (22nd December 2021) - Zhu, Beibei; Gu, Shanshan; Wu, Xiaoting; He, Wenyong; Zhou, Hongke
Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies that seriously threaten global health. The primary reason for its grim prognosis is the lack of sensitive tools for early diagnosis. The purpose of the present study was to apply bioinformatics analysis to explore tumor-educated platelet (TEP) microRNA (miRNA) expression and its potential diagnostic utility in HCC. Methods: Twenty-five HCC patients and 25 healthy controls were included. RNA sequencing was utilized to screen miRNA alterations in platelets derived from HCC patients ( n =5) and controls ( n =5). Gene set enrichment analysis was performed to analyze the targeted mRNAs of differentially expressed miRNAs by using the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, aiming at main functions and pathways, respectively. We then verified the selected platelet miRNAs in another cohort by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) amplification. Results: A total of 250 differentially expressed miRNAs were identified, among which 111 were down-regulated and 139 were up-regulated. The functional enrichment analysis of differentially expressed miRNAs suggested that their target genes were involved primarily in pathways related to HCC. Expression levels of miR-495-3p and miR-1293 were further validated by qRT-PCR, which yielded results consistent with the sequencing analysis. The area under the receiver operating characteristic (ROC) curve of miR-495-3p and miR-1293 as diagnostic tests for HCC were 0.76 and 0.78, respectively. Conclusion: TEP miRNAs such as miR-495-3p and miR-1293 were differentially expressed in HCC patients, and may be involved in the pathophysiology of HCC.